One-Pot Hydrothermal Synthesis, Characterization, and Desulfurization Performance of ZnFe2O4/AC Composites - Hui-qiang Wang; Ming-hua Liu; Xin Luo; Yi-fan Liu; Fei-er Chen; Yuan-cai Lv (Journal of Nanotechnology)
ZnFe2O4/AC composites were prepared by the one-pot hydrothermal method using the activated carbon (AC) as a carrier. The synthesis conditions were optimized by a single-factor experiment. The structural, textural, and surface properties of the adsorbent have been comprehensively characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier-transform infrared (FT-IR) spectroscopy, Brunauer–Emmett–Teller (BET) measurements, and X-ray photoelectron spectroscopy (XPS) analysis. The SO2 removal capacities of the composites were investigated via testing the adsorption capacity at the self-made desulfurization equipment. The results show that the adsorption capacity of ZnFe2O4/AC composites is much higher than that of the AC and ZnFe2O4 samples, respectively. The composite overcomes the disadvantages of the traditional sintering, showing a very high desulfurization performance. The breakthrough time was 147 min, and the sulfur adsorption capacity could reach 23.67% in the desulfurization performance test.